Hepatitis Vaccination of Men Who Have Sex with Men at Gay Pride Events - Storholm, Erik David (Springer US, 2010)
Prevention researchers have advocated primary prevention such as vaccination in alternative venues. However, there have been major questions about both the attendance of, and the ability to, vaccinate high-risk individuals in such settings. The current study seeks to assess the feasibility of vaccinating high-risk men who have sex with men (MSM) at Gay Pride events. The research questions are: Do gay men who are sampled at Gay Pride events engage in more or less risky behavior than gay men sampled at other venues? Do the gay men who receive hepatitis vaccinations at Gay Pride engage in more or less risky behavior than gay men at Gay Pride who do not receive hepatitis vaccination? Of the 3689 MSM that completed the Field Risk Assessment (FRA), 1095/3689 = 29.68% were recruited at either the 2006 or 2007 Long Beach, California Gay Pride events. The remaining, 2594/3689 = 70.32% were recruited at Long Beach gay bars, gay community organizations and institutions, and through street recruitment in various gay enclaves in the Long Beach area. Logistic regression analysis yielded eight factors that were associated with non-attendance of Gay Pride: Age, had sex while high in the last 12 months, had unprotected anal intercourse (UAI) in the last 12 months, had sex for drugs/money in the last 12 months, been diagnosed with a sexually transmitted infection (STI) in the last 12 months, used nitrites (poppers) in the last 12 months, and used methamphetamine in the last 12 months. Identifying as White, Asian, or African American compared to Hispanic was also associated with non-attendance. Bivariate analysis indicated that, of the MSM sampled at Gay Pride, 280/1095 = 25.57% received a hepatitis vaccination there. The MSM sampled at Gay Pride who reported engaging in UAI or having used any stimulant (cocaine, crack-cocaine, or methamphetamine) in the last 12 months were more likely to receive hepatitis vaccination on-site. The results provide evidence for the viability of successfully vaccinating high-risk MSM at Gay Pride events. However, it is vital that no-cost vaccinations are also funded in other community settings such as STI clinics, drug treatment programs, prisons, universities, and other community resource centers in order to reach those additional high-risk MSM who do not attend Gay Pride.